Comparison of interface capturing methods for the simulation of two-phase flow in a unified low-Mach framework. (April 2022) - Boniou, Victor; Schmitt, Thomas; Vié, Aymeric
Abstract: This paper proposes a comparison of four popular interface capturing methods : the volume of fluid (VOF), the standard level set (SLS), the accurate conservative level set (ACLS) and the coupled level set and volume of fluid (CLSVOF). All methods are embedded into a unified low-Mach framework based on a Cartesian-grid finite-volume discretization. This framework includes a sharp transport of the interface, a well-balanced surface tension discretization and a consistent mass and momentum transport which allows capillary-driven simulations with high density ratio. The comparison relies on shared metrics for geometrical accuracy, mass and momentum conservation which exposes the weakness and strengths of each method. Finally, the versatility and capabilities of the proposed solver are demonstrated on the simulation of a 3D head-on collision of two water droplets. Overall, all methods manage to retrieve reasonable results for all test cases presented. VOF, CLSVOF and ACLS tend to artificially create little structures while SLS suffers from conservation issues in the mesh resolution limit. This study leads us to the conclusion that CLSVOF is the most promising method for two-phase flow simulations in our specific framework because of its inherent conservation properties and topology accuracy. Highlights: Comparison of Volume-of-Fluid, Standard Level Set, Accurate Conservative Level Set and Coupled LS/VOF is performed. All methods are integrated into a unified framework, with attention drawn to the surface tension and momentum transport. All methods reach reasonable accuracy with mesh refinement, showing their consistency. LS methods provide the most accurate curvature estimates while VOF methods present the best conservation properties. The versatility of CLSVOF makes it attractive for interface with additional physics such as mass or heat exchanges.